(untitled) (Journal of Technology and Operations Management, 2015)
The purpose of this conceptual paper is to look into the development of green management and technology towards business sustainability. The concept of relationship between green management and technology towards business sustainability is explored. Several important items are focused upon including the role of green management, technology and business sustainability as fundamental factors and their correlation. Theoretically this paper aims to fill the gap on an area of green management, technology and business sustainability which has been rarely touched upon. The definition of the green manufacturing, measurement for the implementation and practice as well as the emergence and its importance is discussed below. The paper contained herein has a strong implication for Malaysian business and also to other countries of the world. It is highly expected that leaders from top to floor level in business organizations will adapt and apply for successfully managing green, technology of green towards sustaining business. The whole function in the organization from the top, middle and lower floor members inclusive of supporting groups such as procurement, material handler, quality and engineering must perform a team effort for making the green management and technology a successful business sustainability.